Advances in cognitive science (2Vol. set) - Srinivasan, Narayanan [ed.]; Gupta, A.K. [ed.]; Pandey, Janak [ed.]; Kar, Bhoomika R. [ed.] (New Delhi Sage, 2008)
Since the coinage of the term by scientist H. Christopher Longuet-Higgins in 1973, Cognitive Science has become a fast growing field of study worldwide, comprising cross-linkages of disciplines like psychology, neuroscience, computer science, linguistics and philosophy. With contributions from eminent scientists from around the globe, Advances in Cognitive Science: Volume 1 covers various sub-disciplines of this study area like Cognitive Processes, Cognitive Neuroscience, Computational Modeling, Cognitive Development and Intervention, Culture and Cognition, and Consciousness. The often neglected issues of culture and cognition, and consciousness are also discussed in detail Table Of Contents: List of Tables ix List of Figures xi List of Abbreviations xv Preface xvii Section I Cognitive Processes Chapter 1 Hierarchical Organization of Complex Visuo-Motor Sequences V.S. Chandrasekhar Pammi S. Bapi Raju Ahmed K.P. Miyapuram Kenji Doya 7 Chapter 2 Orienting Attention and Cued Sustained Attention Indramani L. Singh Pamela M. Greenwood Raja Parasuraman 18 Chapter 3 Why Does Foveal Bias Decrease in the Presence of Additional Element? Muhammad Kamal Uddin Takahiro Kawabe Sachio Nakamizo 31 Chapter 4 New Associative Learning in Amnesia Suparna Rajaram H. Branch Coslett 43 Chapter 5 The Coordinated Processing of Scene and Utterance: Evidence from Eye-Tracking in Depicted Events Pia Knoeferle Matthew W. Crocker 50 Chapter 6 Script Indices Richard Sproat Prakash Padakannaya 62 Chapter 7 How Do We Parse Compound Words? Gary Libben 71 Chapter 8 Other Minds: Social Cognition in Wild Bonnet Macaques Anindya Sinha 87 Section II Cognitive Neuroscience Chapter 9 A Survey of Molecular Mapping as Applied to Studies of the Visual System Avi Chaudhuri 111 Chapter 10 Neural Substrates of Language Processing in Bilinguals: Imagi(ni)ng the Possibilities Jyotsna Vaid 120 Chapter 11 Side Bias in Human Behaviour Manas K. Mandal Hari S. Asthana Ramakrishna Biswal 135 Section II
Keywords: Cognition; Cognitive science